NILAI-NILAI RELIGIUS DALAM KUMPULAN CERPEN ROBOHNYA SURAU KAMI DAN IMPLIKASINYA TERHADAP PEMBELAJARAN DI SMA - Feny Novika Sari; Muhammad Fuad; Sumarti Sumarti (FKIP Universitas Lampung, 2020)
This research purposed to describe the religious values in a collection of short stories Robohnya Surau Kami created by A.A. Navis. This research used descriptive qualitative method. The data of this research are religious values contained in a collection of short stories. The finding of this research showed that in a collection of short stories Robohnya Surau Kami, there are religious values 1) monotheism; 2) fiqh; and 3) morals. The finding of this research can be implied in learning of eleventh grade high school students at basic competence 3.8 identifying values life in a collection of short stories read. It can be seen in the form of teaching materials on the core activities in the implementation of learning lesson plans. Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai religius dalam kumpulan cerpen Robohnya Surau Kami karya A.A. Navis. Penelitian ini menggunakan metode deskriptif kualitatif. Data penelitian ini ialah nilai-nilai religius yang terkandung dalam kumpulan cerpen. Hasil penelitian menunjukkan bahwa dalam kumpulan cerpen Robohnya Surau Kami terdapat nilai-nilai religius 1) tauhid; 2) fikih; dan 3) akhlak. Hasil penelitian ini dapat diimplikasikan dalam pembelajaran SMA kelas XI pada kompetensi dasar 3.8 mengidentifikasi nilai-nilai kehidupan dalam kumpulan cerita pendek yang dibaca. Implikasi ini dapat dilihat dalam bentuk bahan ajar pada bagian kegiatan inti dalam Rencana Pelaksanaan Pembelajaran (RPP).Keywords: Religious value, Short story collection, Implications